2017
DOI: 10.2174/1874944501710010080
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices Regarding Dengue, Chikungunya, and Zika and their Vector Aedes Aegypti in Villavicencio, Colombia

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Other studies corroborated such finding [15, 19, 28]. One study showed that only around 58% of their participants mentioned that Zika was transmitted by any mosquito bite, however, the same study also mentioned that nearly 20% said that the virus is transmitted through Aedes aegypti bite [28]. This study was not able to combine all the responses related to transmission by mosquitoes which, when combined, could have reached 78%.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Other studies corroborated such finding [15, 19, 28]. One study showed that only around 58% of their participants mentioned that Zika was transmitted by any mosquito bite, however, the same study also mentioned that nearly 20% said that the virus is transmitted through Aedes aegypti bite [28]. This study was not able to combine all the responses related to transmission by mosquitoes which, when combined, could have reached 78%.…”
Section: Discussionmentioning
confidence: 78%
“…This can be attributed to high level of awareness of the respondents on Zika Virus Disease mode of transmission as influenced by the tri-media (TV, radio and print). Other studies corroborated such finding [15, 19, 28]. One study showed that only around 58% of their participants mentioned that Zika was transmitted by any mosquito bite, however, the same study also mentioned that nearly 20% said that the virus is transmitted through Aedes aegypti bite [28].…”
Section: Discussionmentioning
confidence: 78%
“…And actions are taken only when being monitored or when there is a death case. Also, possibly some people do perform good practices but quickly became demotivated when they realise their efforts are not matched by their immediate community 68 . Therefore, heightening awareness and good attitude and positive encouragement of subsequent good practices are important.…”
Section: Discussionmentioning
confidence: 99%
“…As both vectors and pathogens continue to arise in novel locations, it is important to understand how residents view emerging diseases compared to endemic ones. To date, yet few KAP studies on the emergent threats of ZIKV and CHIKV have taken place in the Americas, where dengue is considered endemic [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%